Gambaran Pengetahuan Ibu Tentang Imunisasi Hb-0 di TPMB “L” Kabupaten Ciamis - Firdaus, Firna Nakhwa; Fatimah, Siti; Rohmah, Siti; Lestari, Ririn (Journal of Midwifery and Public Health, 2023)
Data from the Ministry of Health of the Republic of Indonesia shows that as many as 7.1% or 18 million Indonesians are infected with Hepatitis B-0. Of these, 50% are at risk of becoming chronic and 900,000 can become liver cancer. Even Hepatitis B-0 is the top 4 cause of death in Indonesia, with an estimated annual death of 51,100 deaths. HB-0 immunization coverage at TPMB "L" in May 2023 is 35% of the target of 100%. The purpose of this study: To determine the picture of maternal knowledge about HB-0 immunization in newborns in TPMB "L". This research method is a descriptive study, sampling using the Accidental sampling method, with a total of 25 respondents of 3rd-trimester pregnant women in TPMB "L" using questionnaires. The results of the study: Pregnant women with quite a lot of knowledge categories are 20 people (80%) and pregnant women with knowledge of approximately 5 people (20%). Conclusion: The level of knowledge about HB-0 immunization in TPMB "L" with sufficient category is 20 respondents (80%). It is expected that health workers, especially midwives, will further increase knowledge of 3rd-trimester pregnant women about HB-0 immunization by providing education through counselling about HB-0 immunization or distributing brochures about the HB-0 immunization program.